Polystyrene microplastic ingestion induces the damage in digestive gland of Amphioctopus fangsiao at the physiological, inflammatory, metabolome and transcriptomic levels. (15th December 2022) - Zheng, Jian; Li, Congjun; Zheng, Xiaodong
Abstract: Microplastics are ubiquitous in the aquatic and terrestrial ecosystem, increasingly becoming a serious concern for aquatic organism health. However, information regarding the effects of microplastics on cephalopods is remain limited to date. Amphioctopus fangsiao, an important economic species in cephalopods, can serve as a potential indicator of environmental pollution due to its short life expectancy and high metabolic rates. Here, to explore the toxic effects during the microplastic stress response, we analyzed the growth performance, histopathological damage, oxidative stress biomarkers, metabolomic and transcriptomic response in digestive gland of A. fangsiao under different concentrations (0, 100 and 1000 μg/L) of commercial polystyrene microplastics (MPS) exposure (5 μm, sphere) for 21 days. The results showed that MPS exerted a huge influence on the growth performance of A. fangsiao . The oxidative stress and inflammation in digestive gland of A. fangsiao were also detected after exposure to MPS. In addition, most of the altered metabolites observed in the metabolic analysis were related to inflammation, oxidative stress and glucolipid metabolism. Transcriptome analysis detected the differentially expressed genes (DEGs) and the significantly enriched KEGG pathways associated with glycolipid metabolism, inflammation and DNA damage. Collectively, our results indicate that excessive environmental microplastic exposure will cause toxicity damage and then initiate the detoxification mechanism in A. fangsiao digestive gland to maintain homeostasis. This study revealed that microplastic can cause adverse consequences on cephalopods, providing novel insights into the toxicological effect of microplastic exposure. Graphical abstract: Image 1 Highlights: MPS exposure reduced the growth performance in octopus. MPS exposure caused histological damage in octopus. MPS exposure caused oxidative stress in octopus. MPS exposure caused metabolic alterations in octopus. DNA damage-related pathways were observed in octopus exposed to MPS.